2017
DOI: 10.1097/fpc.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

TPMT, COMT and ACYP2 genetic variants in paediatric cancer patients with cisplatin-induced ototoxicity

Abstract: We showed an association between the ACYP2 polymorphism and cisplatin-induced ototoxicity, but not with the TPMT and COMT. A meta-analysis was statistically significant for both the COMT rs4646316 and the ACYP2 rs1872328 SNPs. Grading the hearing of children with asymmetric hearing loss requires additional clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 29 publications
(62 reference statements)
2
67
0
Order By: Relevance
“…The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, others were unable to confirm these findings ( Table and Table ). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section “Confounding Factors.” Of note, when excluding cohorts of patients who all received cranial irradiation or that included adult patients, the findings from all but one study showed that TPMT rs12201199 was either significantly more frequent in cases when compared with controls, or trended toward significance ( P = 0.07) . On closer examination of the small cohort of patients ( n = 41) that deviated from the pattern of increased risk, it was observed that only CIO cases carried nonfunctional TPMT*3 alleles.…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, others were unable to confirm these findings ( Table and Table ). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section “Confounding Factors.” Of note, when excluding cohorts of patients who all received cranial irradiation or that included adult patients, the findings from all but one study showed that TPMT rs12201199 was either significantly more frequent in cases when compared with controls, or trended toward significance ( P = 0.07) . On closer examination of the small cohort of patients ( n = 41) that deviated from the pattern of increased risk, it was observed that only CIO cases carried nonfunctional TPMT*3 alleles.…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
“…In addition, ACYP2 is expressed in murine ear cells and decreased ACYP2 expression is associated with increased cisplatin‐induced cytotoxicity . Further support for this variant has been provided by three independent studies that have replicated the association with ACYP2 and CIO . Two studies were, however, unable to replicate these findings ( Table ), the results of which have not yet been recorded in the PharmGKB database.…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ACYP2 (Acylphosphatase 2) gene located on chromosome 2p16.2, encodes a small cytosolic acylphosphatase enzyme that catalyzes the hydrolysis of carboxyl‐phosphate bonds (Wellmann et al, ). Genome wide association study has demonstrated that genetic polymorphisms in ACYP2 are associated with telomere length (He et al, ), which has led to studies of the association between ACYP2 and various diseases, including various cancers (Thiesen et al, ). A recent paper has indicated a significant association between ACYP2 single nucleotide polymorphisms (SNPs) and testicular cancer (Drögemöller et al, ).…”
Section: Introductionmentioning
confidence: 99%